2000
DOI: 10.1128/aem.66.3.1050-1056.2000
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Fe(III), Mn(IV), and Toxic Metals at 100°C by Pyrobaculum islandicum

Abstract: It has recently been noted that a diversity of hyperthermophilic microorganisms have the ability to reduce Fe(III) with hydrogen as the electron donor, but the reduction of Fe(III) or other metals by these organisms has not been previously examined in detail. When Pyrobaculum islandicum was grown at 100°C in a medium with hydrogen as the electron donor and Fe(III)-citrate as the electron acceptor, the increase in cell numbers of P. islandicum per mole of Fe(III) reduced was found to be ca. 10-fold higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(145 citation statements)
references
References 63 publications
3
138
0
3
Order By: Relevance
“…Since the first report on the ability of some Fe(III) reducing bacteria to enzymatically reduce U(VI) (Lovley et al, 1991), the number of known U(VI) reducing microorganisms has increased (Shelobolina et al, 2004;. As shown in Figure 2, more than 25 species of phylogenetically diverse prokaryotes are known to mediate enzymatic U(VI) reduction, including a hyperthermophilic archaeon (Kashefi and Lovley, 2000), thermophilic bacteria (Kieft et al, 1999), mesophilic Fe(III) reducing bacteria (Lovley et al, 1991, Coates et al, 1998Coates et al, 2001), mesophilic sulfate reducing bacteria (Lovley and Phillips, 1992;Lovley et al, 1993;Tebo and Obraztsova, 1998;Suzuki et al, 2005), fermentative bacteria (Francis et al, 1994;Sani et al, 2002), a heterotrophic bacterium (McLean and Beveridge, 2001), and an acidotolerant bacterium (Shelobolina et al, 2004). Some of these have been shown to grow using U(VI) as a sole terminal electron acceptor (Lovley et al, 1991;Tebo and Obraztsova, 1998;Pietzsch et al, 1999).…”
Section: Direct Enzymatic Control Of the Redox Transformations Of Umentioning
confidence: 99%
“…Since the first report on the ability of some Fe(III) reducing bacteria to enzymatically reduce U(VI) (Lovley et al, 1991), the number of known U(VI) reducing microorganisms has increased (Shelobolina et al, 2004;. As shown in Figure 2, more than 25 species of phylogenetically diverse prokaryotes are known to mediate enzymatic U(VI) reduction, including a hyperthermophilic archaeon (Kashefi and Lovley, 2000), thermophilic bacteria (Kieft et al, 1999), mesophilic Fe(III) reducing bacteria (Lovley et al, 1991, Coates et al, 1998Coates et al, 2001), mesophilic sulfate reducing bacteria (Lovley and Phillips, 1992;Lovley et al, 1993;Tebo and Obraztsova, 1998;Suzuki et al, 2005), fermentative bacteria (Francis et al, 1994;Sani et al, 2002), a heterotrophic bacterium (McLean and Beveridge, 2001), and an acidotolerant bacterium (Shelobolina et al, 2004). Some of these have been shown to grow using U(VI) as a sole terminal electron acceptor (Lovley et al, 1991;Tebo and Obraztsova, 1998;Pietzsch et al, 1999).…”
Section: Direct Enzymatic Control Of the Redox Transformations Of Umentioning
confidence: 99%
“…, extremophiles (e.g., Thermoanaerobacter spp. (Roh et al, 2002) and Pyrobaculum islandicum (Kashefi and Lovley, 2000)) as well as Gram-positive non-spore-forming bacteria (e.g., Thermoterrabacterium sp.) (Khijniak et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Under anaerobic conditions, this organism grows with elemental sulfur, thiosulfate, glutathione (oxidized form) or L-cystine as terminal electron acceptor (Sako et al, 2001). From the aspect of respiration, the genus Pyrobaculum is uniquely variable among the hyperthermophilic archaea, which may be closest to the common ancestor of all organisms; P. aerophilum is not only a microaerophile but also a nitrate, nitrite, thiosulfate, arsenate and selenite reducer (Völkl et al, 1993;Huber et al, 2000); Pyrobaculum islandicum reduces sulfur and iron(II) compounds (Huber et al, 1987;Kashefi & Lovely, 2000;Vargas et al, 1998); Pyrobaculum organotrophum reduces sulfur compounds (Huber et al, 1987); Thermoproteus neutrophilus, which is classified in the genus Thermoproteus although the phylogenetic analysis of 16S rDNA indicated that it should be reclassified as a Pyrobaculum species (Ito et al, 1998), is a sulfur reducer (Fischer et al, 1983); Pyrobaculum arsenaticum is arsenite reducer . This diversity of respiration in close relatives suggests that this genus may show a good example of the evolution of respiration and also show the nature of adaptation to the aerobic environment.…”
Section: Introductionmentioning
confidence: 99%